Similarity or Difference? The Relation between Structure and Strategy Isomorphism in Public Organizations. (7th August 2013) - Villadsen, Anders R.
Abstract : While the organizational structures and strategies of public organizations have attracted substantial research attention among public management scholars, little research has explored how these organizational core dimensions are interconnected and influenced by pressures for similarity. In this paper I address this topic by exploring the relation between expenditure strategy isomorphism and structure isomorphism in Danish municipalities. Different literatures suggest that organizations exist in concurrent pressures for being similar to and different from other organizations in their field of action. It is theorized that to meet this challenge organizations may substitute increased similarity on one core dimension for increased idiosyncrasy on another, but only after a certain level of isomorphism is reached. Results of quantitative analyses support this theory and show that an inverse U‐shaped relation exists between expenditure strategy isomorphism and structure isomorphism in a longitudinal quantitative study of Danish municipalities.